The Idea of Festival in Construction Education in Architecture - Atakara, Cemil; Hurol, Yonca (EAAE, 2004)
The aim of this article is to introduce the idea of festival which can be used during the construction courses in architecture.
This is an interdisciplinary article which combines technological issues, such as construction, with education techniques which support design education.
Keywords: architectural education, construction courses, idea of festival